Potencial en recursos turísticos del centro poblado Rica Playa – Tumbes, para la práctica del turismo rural - Romero Córdova, Neiser Homero (2017)
The practice of tourism in rural areas is experiencing an increasing trend in the world. The main objective has been to analyze the potential in terms of natural and cultural tourism resources and the attitude of the local population, the Village Center of Rica Playa, San Jacinto District, Tumbes province and region, for the practice of tourism in rural areas. The present descriptive applied qualitative study was performed through the application of ethnographic, analytical-synthetic and inductive-deductive methods, and techniques such as direct observation, interview and survey; Supported by information collection instruments such as evaluation sheets, observation and interview guides, and survey questionnaire. The object of study was the potential in tourism resources. The data were collected from the territory of the locality in the case of natural resources, and a total sample of 150 people in the case of cultural resources, and of these 15 ethnographic interviews. The most salient results in Rica Playa are expressed in the diversified presence of the natural and cultural potential as tourist resources that configure the scenarios of the natural landscape of different biodiversity spaces, and the cultural landscape that changes during the year related to seasonal and permanent crops By the presence of traditional livestock activities and the practice of local folklor. As well as a broad knowledge about their natural and cultural environment that supports the responsible attitude with positive expectations of the receiving community for the practice of rural tourism, still persisting the weakness in the tourist organization by the settlers